Лето любви: роман / Румелия Лейн - Лейн Румелия (Цветы любви, 2003)
Экземпляры: ф.13 (2005) / Инвентарный номер: 49104 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Л 42 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44